Pro Visual C++/CLI and the .NET 3.5 Platform - R. G. Fraser, Stephen (Apress, 2012)
This book is for Visual C++ programmers who don’t care about COM, DCOM, COM+, or ActiveX components, either because they already know them or because they never had any reason to learn to code them. You’ll use a pure .NET development environment. The only time you’ll use components is when you access them—a necessary evil, as there are thousands of them out there that may never be converted to .NET.